2019
DOI: 10.1186/s12944-019-0996-5
|View full text |Cite
|
Sign up to set email alerts
|

Monoraphidium sp. HDMA-20 is a new potential source of α-linolenic acid and eicosatetraenoic acid

Abstract: Background ω-3 polyunsaturated fatty acids (PUFAs) are synthesized from α-Linolenic acid (ALA, C18:3ω3) and play important roles in anti-inflammatory and antioxidant responses in mammal cells. ALA is an essential fatty acid which cannot be produced within the human body and must be acquired through diet. The purpose of this study was to evaluate the potential of a novel microalgal strain (HDMA-20) as a source of ω-3 PUFAs including ALA and eicosatetraenoic acid (ETA, C20:4ω3). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…KMN5; 13.0 mg L −1 d −1 ) (Tale et al, 2014), Monoraphidium sp. HDMA-20; 36.3 mg L −1 d −1 ) (Lin et al, 2019). A recent study by our group involving Parachlorella kessleri subjected to a nitrogen stress condition demonstrates that the photosynthetic activity ceases affecting the phosphorus absorption, and cells shut down energy-expensive metabolisms, such as protein synthesis, by diverting the carbon flux to energy storage metabolites, such as lipids and/or carbohydrates (Shaikh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…KMN5; 13.0 mg L −1 d −1 ) (Tale et al, 2014), Monoraphidium sp. HDMA-20; 36.3 mg L −1 d −1 ) (Lin et al, 2019). A recent study by our group involving Parachlorella kessleri subjected to a nitrogen stress condition demonstrates that the photosynthetic activity ceases affecting the phosphorus absorption, and cells shut down energy-expensive metabolisms, such as protein synthesis, by diverting the carbon flux to energy storage metabolites, such as lipids and/or carbohydrates (Shaikh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Третім видом, виявленим у зразках води, був Monoraphidium sp. Клітини цієї зеленої мікроводорості мають викривлену форму та утворюють колонії з кількох клітин (Lin et al, 2019). Рибний ставок можна вважати хорошим місцезростанням для Monoraphidium sp., оскільки у його воді міститься багато поживних речовин, таких як азот, фосфор і залізо.…”
Section: Chlorella Spunclassified
“…Since ω-3 PUFAs cannot be de novo synthesized by mammals, they must be obtained through diet. Due to the vital role of eicosapentaenoic acid (EPA, 20:5 ω-3) and docosahexaenoic acid (DHA, 22:6 ω-3) in human health, they received growing attention and were well-studied in recent years [3,4]. In addition, stearidonic acid (SDA, 18:4 ω-3) and docosapentaenoic acid (DPA, 22:5 ω-3) have been developed and utilized [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been known as a metabolic precursor of EPA. Various research has been conducted on the health benefit of EPA and DHA, while the detailed biochemical function of ETA has rarely been reported since it is a rare source and cannot be easily purified [4]. Early studies indicated that ETA could modulate eicosanoid production in mammalian cell systems and works as an active molecule responsible for anti-inflammatory responses [1,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation